POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG TENTANG SISTEM PERADILAN PIDANA ANAK : UPAYA MENJAUHAKAN ANAK DARI PIDANA PENJARA - Saputra, Trias (IBLAM LAW REVIEW, 2022)
This study aims to review and discuss the mechanism for imposing penalties/criminals for children who are in conflict with the law as regulated in Law Number 11 of 2012 concerning the Child Criminal Justice System. In the Law there are changes to the provisions for imposing penalties/criminals for children. Imprisonment is placed at the last order in this provision. different from the Regulations regulated in the Previous Law. This study will also discuss the process of forming the SPPA Law in the Political-Legal aspect which examines the minutes of the Formation of Legislations and the academic text of the Law. The method used in this research is juridical-normative by using secondary data or library data (library research) with the approach to legislation (The Statute Approach).